2014
DOI: 10.1063/1.4863503
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of large amplitude plasma blobs in three-dimensions

Abstract: Fluctuations in fusion boundary and similar plasmas often have the form of filamentary structures, or blobs, that convectively propagate radially. This may lead to the degradation of plasma facing components as well as plasma confinement. Theoretical analysis of plasma blobs usually takes advantage of the so-called Boussinesq approximation of the potential vorticity equation, which greatly simplifies the treatment analytically and numerically. This approximation is only strictly justified when the blob density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…The Boussinesq approximation gives reasonably accurate results for blobs with moderate blob to ambient plasma density ratio. 13 Finite ion temperature effects can enhance polarization drift, modifying the blob propagation speed. 9 For the case of large blob to ambient plasma density ratio,ñ=n 0 , the finite ion temperature may dominate standard vorticity term, r Á ½enr ?…”
Section: A Governing Equationsmentioning
confidence: 99%
“…The Boussinesq approximation gives reasonably accurate results for blobs with moderate blob to ambient plasma density ratio. 13 Finite ion temperature effects can enhance polarization drift, modifying the blob propagation speed. 9 For the case of large blob to ambient plasma density ratio,ñ=n 0 , the finite ion temperature may dominate standard vorticity term, r Á ½enr ?…”
Section: A Governing Equationsmentioning
confidence: 99%
“…so that, by substitution of equation (18) into equation (21) and then by substitution into equation (20) an expression for the sheath heat flux is given by…”
Section: Rc ∂ ∂Zmentioning
confidence: 99%
“…The velocities in each regime, alongside the fundamental filament size vary as the temperature and density in the filament change (keeping pressure fixed) with a general increase as the temperature is increased and the density decreased. Angus et al [21] and Omotani et al [18] have recently shown that, with the Boussinesq assumption relaxed the inertial regime velocity scaling is better represented by taking Figure 1. Scaling of the 2D filament characteristic velocity in the inertial regime (IL, broken lines) calculated from equation (30) and in the sheath limited regime (SL, solid lines) calculated from equation (31) for the following cases: δn = 2, δT = 0 (red), δn = 1, δT = 1 (black) and δn = 0, δT = 2 (blue).…”
Section: Velocity Scalingmentioning
confidence: 99%
“…For low collisionality, the electric potential in the blob evolves towards establishment of a Boltzmann relation in phase with the electron density along B, so that n e ∼ exp(−φ) ∼ φ. This leads to reduced radial particle transport, and the resulting spatial alignment of the potential with the blob density perturbation produces a rotating vortex along contours of constant density, the so-called Boltzmann spinning [33,34]. Large collisionality leads to a delay in the build-up of the potential within the blob, so that the radial interchange driving can compete with the parallel evolution, and the perpendicular propagation is similar to the 2-d scenario.…”
Section: Three-dimensional Filament Computationsmentioning
confidence: 99%